A visualização matemática em jogos educacionais digitais no Brasil - Cruz, Paulo Fernando Costa da [UNESP] (2025)
The main objective of this research is to contribute to Mathematics Education in the study of the application of mathematical visualization in digital educational games. The specific objectives are to carry out a bibliographical research, in the form of a systematic review of the literature, to verify the existence of academic texts in Brazil, from 2019 to 2023, that report the use of digital games that apply mathematical visualization and , also, carrying out an experiment to develop a digital educational game with a strong emphasis on mathematical visualization with the qualitative evaluation of the effects of applying mathematical visualization on students through this game, carried out by educators linked to the teaching of mathematics. The problem to be studied took the form of the following research question: The application of mathematical visualization in digital educational games brings, to students, motivation, entertainment, understanding of mathematics, stimulation of logical reasoning and help in solving problems and, therefore, can it be considered effective for learning mathematics? In an attempt to find a solution to the proposed problem, preexperimental research was developed, of an applied nature, with a descriptive objective and a qualitative approach, which consisted of the development of a digital educational game and its evaluation by educators linked to the area of mathematics. The results of the experiment were not entirely convincing, as at one point the educators attributed the effects on students to mathematical visualization and at another to the game. Therefore, we suggest carrying out further and more precise research to truly verify the value of applying this Mathematics Education technique through digital educational games. Possibly, carrying out experimental research, with samples sized by statistical techniques and the use of more variables, could in the future establish a clearer panorama about the value of using mathematical visualization in digital educational games, contributing to the development of this technique.